IMPACT OF SERVICE AND FOOD QUALITY ON CUSTOMER SATISFACTION AMONG GENERATION Y FOR THE FAST FOOD RESTAURANT IN MALAYSIA (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The drive of this study is to contribute to the literature of service and food quality significance in fast food restaurant industryof Malaysia. The study is carrying out from the viewpoint of fast food restaurant industry and the customers' satisfaction among generation Y in Malaysia. Three variables have been examined to demonstrate the significance of service quality and food quality on customer satisfaction. The outcomesratify the importance of greatercorresponding service and food standards in fast food restaurant industry. For food quality factor, allrespondents are agreed with statement. Findings from 1000 respondents of Generation Yshowed that two factors significantlyinfluenced customer satisfaction. Thisresearch would be valuable in the improvement of a more comprehensive model to simplify a better understanding of customers' satisfaction among generation Y on fast food restaurant in Malaysia; these findings would deliver a better comprehension of Malaysian customers' satisfaction andhelp design more effective marketing strategies